Review on quantification vitamin B12 in blood - Das, Priyabrata; Daronde, Subodh (Journal of Neonatal Surgery, 2025)
Vitamin B12 is one of the micronutrients that are required in the formation of blood cells, the functions of the nervous systems and also the synthesis of DNA. Importantly, Vitamin B12 level in blood should be measured precisely for detecting deficiencies and monitoring therapeutic interventions. Some of the quantification methods that have been discussed in this review paper include chemiluminescent immunoassays, LC-MS/MS and electrochemiluminescence immunoassays alongside their performance in terms of their efficiency, sensitivity, specificity, and feasibility. These evaluations are the primary objective of this review paper as well. Through a thorough analysis of recent studies, the technological innovations and methodological refinements that have enhanced the accuracy and reliability of vitamin B12 measurements are highlighted clearly. By bringing together all the existing research findings and identifying areas that need more investigation, the current review paper is prepared efficiently thereby providing guidance for both future research and clinical practices as well. Notably, the ongoing discussion regarding the improvement of Vitamin B12 measurement methods and its significance in clinical diagnostics is explained well in this review paper by referencing key studies from 2019 to 2024